Penelusuran Fly Paper Effect pada Belanja Operasi dan Belanja Modal Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Tengah - Ari Junaedi; Gregorius N Masdjojo (Jurnal Ekonomi dan Bisnis, 2022)
This research examine the flypaper effects as one as the indicator of succes of decentralisations. The research analyze to find out wether Balancing Fund (especially General Fund Transfer) and The locally-generated revenur influence the Operational Expenditure and Capital Expenditure in the period of 2018-2020. The resources of data used are budget realization report of 35 Regency/City Regional Government Province of Central Java that was published at the Directorate General of Financial Balance Ministry of Finance. The method used in this study is a purposive sampling method with panel data which is used the combination period/years of 2018-2020 time series data and used the cross section data of 35 Regency/City Regional Governments in Province of Central Java. The result of research prove that there has been a flypaper effect on the Balancing Fund (especially General Fund Transfer) on Operational Expenditures at 35 Regency/City Regional Government in Province of Central Java. The Balancing Fund and Locally Generated Revenue each have a significant influence on Operational Expenditures. The results of the second hypothesis testing prove that the The Balancing Fund and Locally Generated Revenue have no effect on Capitall Exspenditures.